Friends’ Support, Motivation to Learn, Emotional Adjustment, and Academic Performance among Indonesian First-year students - Shanti, Theresia Indira; Janssens, J.M.A.M.; Setiadi, Bernadette (Jurnal Psikologi, 2021)
First-year students face academic and social challenges which will undermine their motivation to learn and emotional adjustment. Friends’ support helps them to cope which then influences their academic performance. This study aimed to investigate relations between friends’ support and academic performance, as mediated by a motivation to learn and emotional adjustment. Participants were 327 first-year university students at the end of their first year, recruited from random cluster sampling. Datawereanalyzed using Sobel Test indicated that motivation to learn and emotional adjustment fully mediated the relationship between friendship quality and academic performance, between lack of intimacy with friends and academic performance, and between conflict with friends and academic performance. Friends provide support which enables students to have discussion to solve their difficulties in facing academic challenges and to disclose their thoughts and feelings to face their emotional challenges. We recommend that further studies collect the data from students in each year and universities to design a curriculum that promotes supportive collaboration among students.